LPIAT1/MBOAT7 depletion increases triglyceride synthesis fueled by high phosphatidylinositol turnover. Issue 1 (6th April 2020) - Tanaka, Yuki; Shimanaka, Yuta; Caddeo, Andrea; Kubo, Takuya; Mao, Yanli; Kubota, Tetsuya; Kubota, Naoto; Yamauchi, Toshimasa; Mancina, Rosellina Margherita; Baselli, Guido; Luukkonen, Panu; Pihlajamäki, Jussi; et al.
Abstract : Objective: Non-alcoholic fatty liver disease (NAFLD) is a common prelude to cirrhosis and hepatocellular carcinoma. The genetic rs641738 C>T variant in the lysophosphatidylinositol acyltransferase 1 ( LPIAT1)/membrane bound O-acyltransferase domain-containing 7, which incorporates arachidonic acid into phosphatidylinositol (PI), is associated with the entire spectrum of NAFLD. In this study, we investigated the mechanism underlying this association in mice and cultured human hepatocytes. Design: We generated the hepatocyte-specific Lpiat1 knockout mice to investigate the function of Lpiat1 in vivo. We also depleted LPIAT1 in cultured human hepatic cells using CRISPR-Cas9 systems or siRNA. The effect of LPIAT1-depletion on liver fibrosis was examined in mice fed high fat diet and in liver spheroids. Lipid species were measured using liquid chromatography-electrospray ionisation mass spectrometry. Lipid metabolism was analysed using radiolabeled glycerol or fatty acids. Results: The hepatocyte-specific Lpiat1 knockout mice developed hepatic steatosis spontaneously, and hepatic fibrosis on high fat diet feeding. Depletion of LPIAT1 in cultured hepatic cells and in spheroids caused triglyceride accumulation and collagen deposition. The increase in hepatocyte fat content was due to a higher triglyceride synthesis fueled by a non-canonical pathway. Indeed, reduction in the PI acyl chain remodelling caused a high PI turnover, by stimulating at the same time PI synthesis and breakdown. The degradation of PI was mediated by a phospholipase C, which produces diacylglycerol, a precursor of triglyceride. Conclusion: We found a novel pathway fueling triglyceride synthesis in hepatocytes, by a direct metabolic flow of PI into triglycerides. Our findings provide an insight into the pathogenesis and therapeutics of NAFLD.